Adipose progenitor cell-derived extracellular vesicles suppress macrophage M1 program to alleviate midlife obesity - Qing Zhou; Jia Gao; Guorao Wu; Chenwei Wang; Yan Yang; Teng Huang; Yi Wang; Tiantian Yue; Zhichao Gao; Hao Xie; Fei Xiong; Ke Xiang; et al. (Nature Communications)
Abstract Among different age groups, middle-aged individuals are particularly susceptible to obesity, with a 22% higher risk of all-cause mortality. However, the underlying mechanisms remain unclear. In this study, we identify adipose progenitor cells (APCs) in the white adipose tissue (WAT) of middle-aged subjects as potential causes of midlife obesity. Specifically, the extracellular vesicles (EVs) derived from APCs display an impaired ability to mitigate the inflammaging of adipose tissue macrophages (ATMs) in middle-aged individuals. Mechanistically, these EVs, lacking miR-145-5p, fail to suppress the expression of L-selectin in ATMs, thereby facilitating their M1 program via the NF-κB signaling pathway. In contrast, EVs from young APCs effectively inhibit M1 macrophage polarization. Accordingly, targeted liposomes are designed to deliver miR-145-5p mimics to ATMs, which effectively prevent the obesity in middle-aged mice. Collectively, our findings highlight the role of APC-derived EVs in midlife obesity and propose miR-145-5pas a promising therapeutic target for clinical applications.